University-Industry Collaboration: Barriers to Commercialization - Mohd Ghazali, Maarof; Sorooshian, Shahryar; Syed Radzi, Rahamaddulla (2016)
This paper identifies the potential barriers that can affect effective collaboration between industry and public university in Malaysia. Intense global competition has created new requirements to the industry: constant new technological breakthrough, rapid deployment of new technological solutions and shorter product life-cycle. Thus, both the industry and the university need to look into possibilities of sharing knowledge-based capital, technological facilities and access to new scientific development and innovation. Data for this study was obtained through interviews with top management of companies involved in providing training, agriculture and solar energy, fund management and manufacturing which have experience in doing collaboration with Malaysian public universities. Later, the data was analyzed using thematic analysis. Among the barriers identified were products are not market driven, bureaucracy, insufficient experience on applied research, lack of proper SOP, unattractive reward system, lack of information on potential collaboration opportunities and Intellectual Property (IP) issues.